2020
DOI: 10.1021/acs.jpcb.9b11051
|View full text |Cite
|
Sign up to set email alerts
|

Li Coordination of a Novel Asymmetric Anion in Ionic Liquid-in-Li Salt Electrolytes

Abstract: We analyze the influence of the asymmetry of the anion on coordination and transport processes in a Li salt/ionic liquid system. The relatively new asymmetric 2,2,2-trifluoromethylsulfonyl-N-cyanamide (TFSAM) anion was investigated in Pyr14TFSAM(1–x)LiTFSAM x over a broad concentration range (up to x = 0.7 Li salt) and was compared to the well-known bis­(trifluoromethanesulfonyl)­amide (TFSA) anion. In contrast to the TFSA-based system, the system with TFSAM has no phase transition over the whole concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
69
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(88 citation statements)
references
References 49 publications
17
69
0
2
Order By: Relevance
“…[ 44 ] In this context, a comparison to the corresponding system with the asymmetric anion TFSAM is interesting. [ 13 ] There, Li + coordination with the strongly interacting CN group is preferred, whereas coordination to the more weakly interacting TFSI group does not occur at all up to a Li salt fraction above 0.3. This more pronounced asymmetry is arising, as in TFSAM, the smaller functional group provides stronger coordination, whereas in FTFSI, the bulkier functional group has a stronger Li + coordination.…”
Section: Local Li+ Coordination Structurementioning
confidence: 99%
See 1 more Smart Citation
“…[ 44 ] In this context, a comparison to the corresponding system with the asymmetric anion TFSAM is interesting. [ 13 ] There, Li + coordination with the strongly interacting CN group is preferred, whereas coordination to the more weakly interacting TFSI group does not occur at all up to a Li salt fraction above 0.3. This more pronounced asymmetry is arising, as in TFSAM, the smaller functional group provides stronger coordination, whereas in FTFSI, the bulkier functional group has a stronger Li + coordination.…”
Section: Local Li+ Coordination Structurementioning
confidence: 99%
“…One example is the 2,2,2‐trifluoromethylsulfonyl‐ N ‐cyanoamide (TFSAM) anion with asymmetric coordination properties, combining the functional groups of bis(trifluoromethanesulfonyl)imide (TFSI) and dicyanamide (DCA). [ 12,13 ] Furthermore, Giffin et al introduced the FTFSI anion, which combines the terminal groups of TFSI and FSI, in IL‐in‐salt systems and demonstrated that it hinders the crystallization at sample concentrations of up to 65 mol% Li salt at room temperature. [ 14 ]…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of different anions will allow for more electrolyte tunability. For example, the asymmetric TFSAM anion promotes single Li + hopping due to higher structural diffusion and is capable of inhibiting crystallization over a broader temperature range when compared to TFSI [180]. In addition, alternative anions can be utilized to synthesize ILs suitable for electrodeposition, such as C 4 mpyrDCA, which has been utilized to deposit Ge thin films [199].…”
Section: Discussionmentioning
confidence: 99%
“…This study highlighted the effectiveness of Li + mobility within C 4 mpyr-based ILs, which is why extensive research has been carried out using C 4 mpyr-based electrolytes with those and trifluoromethanesulfonyl-N-cyanoamide (TFSAM) anions. Recently, TFSAM has been utilized as an anion due to its ability to inhibit crystallization over a broader temperature range when compared to TFSI [180]. The asymmetric TFSAM anion, promotes single Li + hopping due to higher structural diffusion that occurs as the LiTFSAM salt concentration increases [180].…”
Section: Tfsam-anion Studiesmentioning
confidence: 99%
See 1 more Smart Citation